2011
DOI: 10.9724/kfcs.2011.27.6.783
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adding Lotus Root and Leaf Powder on the Quality Characteristics of Cooked Pork Patties

Abstract: This study was carried out to investigate the effects of adding lotus root and leaf powder on the quality characteristics of cooked pork patties. The patties were of four types: unadulterated (control, T0), 0.5% lotus root powder (T1), 0.25% lotus root and 0.25% lotus leaf powder (T2), and 0.5% lotus leaf powder (T3). We found that the moisture content was highest in T1 group, and that the protein and fat contents were lowest in T1 (p<0.05). The ash content was lowest in T0 (p<0.05). The cooking yield and mois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Fat contents of the control and treatments were 21.42 g/100 g and 20.38-20.56 g/100 g, respectively. Similarly, Jung et al (2011) have reported that the addition of 0.5% of lotus rhizome has increased moisture and ash contents but decreased fat and protein contents of cooked pork patty. In general, previous studies have also reported that the addition of dietary fiber to emulsified meat products has increased moisture content but decreased fat content due to high water absorption ability of dietary fiber ( Fernández-Ginés et al , 2004 ; Lee et al , 2008 ).…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…Fat contents of the control and treatments were 21.42 g/100 g and 20.38-20.56 g/100 g, respectively. Similarly, Jung et al (2011) have reported that the addition of 0.5% of lotus rhizome has increased moisture and ash contents but decreased fat and protein contents of cooked pork patty. In general, previous studies have also reported that the addition of dietary fiber to emulsified meat products has increased moisture content but decreased fat content due to high water absorption ability of dietary fiber ( Fernández-Ginés et al , 2004 ; Lee et al , 2008 ).…”
Section: Resultsmentioning
confidence: 87%
“…The addition of lotus rhizome powder did not alter the pH value of meat batter or cooked sausage (5.99-6.05 and 6.04-6.11, p >0.05). Similarly, Jung et al (2011) have reported that the inclusion of 0.5% lotus rhizome has no effect on pH of cooked pork patty. Huang et al (2011) have also noted that the inclusion of 3% lotus rhizome extract does not change the pH of cooked ground pork.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations